2022
DOI: 10.1155/2022/4522493
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Anthropometric Indices in Differential Prediction of Prehypertension and Hypertension in Mexican Population: Results according to Age and Sex

Abstract: Background. Hypertension (HTN) is recognized as a significant public health problem in the world. The objective of this study is to evaluate emergent anthropometric indices as predictors of preHTN and HTN according to age and sex in a sample of Mexican adults. Methods. A cross-sectional study was conducted in 1,150 participants aged 18–80 years old. Anthropometric data and blood pressure measurements were analyzed. Comparisons between men and women were carried out by independent analysis. Cutoff points for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It is worth noting that the calculation of the new anthropometric index BRI is complex compared to traditional AHIs with the addition of WC and Height, but better re ects visceral adipose tissue and body fat [26]. Several cross-sectional studies have shown that BRI levels exhibit strong associations with blood pressure in Mexican populations [30]; another study based on a Chinese population similarly showed a strong correlation between BRI and the development of hypertension in non-obese populations [20]; Wu et al demonstrated that among non-Hispanic whites, non-Hispanic blacks, and other populations, only non-Hispanic whites had a strong association between BRI and hypertension (P for interaction < 0.05) [31]; Xiao et al also noted that the strength of the association between BRI and hypertension was greater in men and urban populations compared with women and rural populations (P < 0.05) [32]. The results of a longitudinal study based in China showed that the risk of hypertension increased with increasing BRI, and the risk of new-onset hypertension was greater in participants < 40 years of age (P for interaction < 0.05) [26].…”
Section: Disscussionmentioning
confidence: 99%
“…It is worth noting that the calculation of the new anthropometric index BRI is complex compared to traditional AHIs with the addition of WC and Height, but better re ects visceral adipose tissue and body fat [26]. Several cross-sectional studies have shown that BRI levels exhibit strong associations with blood pressure in Mexican populations [30]; another study based on a Chinese population similarly showed a strong correlation between BRI and the development of hypertension in non-obese populations [20]; Wu et al demonstrated that among non-Hispanic whites, non-Hispanic blacks, and other populations, only non-Hispanic whites had a strong association between BRI and hypertension (P for interaction < 0.05) [31]; Xiao et al also noted that the strength of the association between BRI and hypertension was greater in men and urban populations compared with women and rural populations (P < 0.05) [32]. The results of a longitudinal study based in China showed that the risk of hypertension increased with increasing BRI, and the risk of new-onset hypertension was greater in participants < 40 years of age (P for interaction < 0.05) [26].…”
Section: Disscussionmentioning
confidence: 99%
“…Many other indexes obtained from anthropometric or mixed anthropometric plus biochemical parameters have been used in different populations to evaluate cardiometabolic risk [8,[37][38][39][40]; however, some show wide individual errors and a lack of sensitivity in detecting change in body fat over time [41], and it is not yet fully clear which emergent anthropometric index may be best associated with cardiometabolic risk and if these vary according to sex and age [40].…”
Section: Anthropometric Markersmentioning
confidence: 99%